Self-assembled theranostic microcarrier targeting tumor cells with high metastatic potential - Xiqi Ma (Elsevier, 2021)
Compared with primary and local tumor, metastasis is more difficult to resect completely and remain the leading cause of death associated with solid tumors. It is therefore pressing to develop effective strategies to prevent and suppress tumor metastasis in its early stages. Heparanase overexpression is significantly associated with increased malignancy and metastasis. Here, we develop a novel heparanase degradable heparin-based microcarrier, HBMA, for specific staining, targeting, and inhibiting tumor cells with high metastatic potential. HBMA is fabricated through self-assembling of three components, positively charged fluorescent gold nanoclusters (KG-AuNCs), heparin polymers (HP), and antisense miRNA-21 oligonucleotides (AM-21), with each component playing multiple roles. Results of confocal microscopy and flow cytometry show that this agent has an excellent capability to label metastatic tumor cells with high selectivity. On the therapeutic side, the results of cell viability assay, wound healing assay, and plate colony formation assay verify that HBMA induces a significant inhibition effect towards the proliferation and migration of the selectively target tumor cells. The heparanase responsive AM-21 delivery, the specific staining, and the efficient tumor cell activity suppression highlight HBMA as a promising cancer theranostic agent to prevent tumor metastasis.